UNDERSTANDING AND RISK IN CA CERVIX WOMEN OF CHILDBEARING AGE IN INDONESIA - Wulandari, Atik (Universitas Wijaya Kusuma Surabaya, 2010)
Because 85% of cancer cases in the world, numbering around 493 000 to 273 000 deaths, occur in developing countries. And Indonesia is the number of patients with cervical cancer has the second largest after China. It is necessary to factor determines the approximately what terytama largest contributor to the founder of the world, especially in Indonesia.After reviewing the literature-based literature and several studies have been done dibeberaspa note that many events where Cervix ca nothing to do with the low level of maternal knowledge about Ca cervix high risk, particularly on cervical Ca risk factors and possible prevention of bias carried out. For that need to be encouraged socialization matters related to the Ca cervix in general to the community and especially to iwanita age range 20-30 years, because it shows that cervical cancer occurs at age 31-60 years.